2015
DOI: 10.1038/nphys3373
|View full text |Cite
|
Sign up to set email alerts
|

Translation correlations in anisotropically scattering media

Abstract: Controlling light propagation across scattering media by wavefront shaping holds great promise for a wide range of communications and imaging applications. However, finding the right wavefront to shape is a challenge when the mapping between input and output scattered wavefronts (i.e. the transmission matrix) is not known. Correlations in transmission matrices, especially the so-called memory-effect, have been exploited to address this limitation. However, the traditional memory-effect applies to thin scatteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
174
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 37 publications
8
174
0
Order By: Relevance
“…However, in real animal systems, the goal is to focus inside the turbid media rather than through it, and we do not have any degree of freedom to control the distance between the scatterer and the target plane. In this case, recent studies have demonstrated that the translational 53 and angular memory effects 55 will both be in play, which has not yet been fully explored. Further utilizations of optical properties can also enable to address existing challenges in in vivo imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in real animal systems, the goal is to focus inside the turbid media rather than through it, and we do not have any degree of freedom to control the distance between the scatterer and the target plane. In this case, recent studies have demonstrated that the translational 53 and angular memory effects 55 will both be in play, which has not yet been fully explored. Further utilizations of optical properties can also enable to address existing challenges in in vivo imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This range is a function inversely related to the degree of scattering and the thickness of the turbid media L, 45,53 or proportional to λ l * s /L as recently verified. 54 According to these prior studies, biological tissues are turbid media and are good for the memory effect due to their relatively high l * s .…”
Section: Imaging Through Biological Tissuesmentioning
confidence: 99%
“…The existence of both single peaked localized states and multiply peaked necklace states has been observed in layered media 46 , single mode waveguides 47 , natural materials 48 , and can be created in multimode optical fiber with mode coupling 49 . It is also of great interest to explore the disposition of energy within thin anisotropic scattering media, of importance in biomedical research 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Strongly anisotropic media, such as biological tissue, also exhibit the translational memory effect, which may be exploited to further the fidelity of imaging through scattering layers [26].…”
Section: Discussionmentioning
confidence: 99%